Stories of Childhood and Adolescence: An Ethnographic Study of Indonesian-Chinese People - Ni Komang Ariani; Sri Nitta Crissiana Wirya Atmaja; Sri Putri Winingrum W A (Universitas Cokroaminoto Palopo, 2023)
James P. Spradley (2006) argues that a language is a tool for constructing reality. The term of non-indigenous for Indonesian-Chinese people continuously exists, even though they are legally Indonesian. It cannot be denied that friction between Indonesian-Chinese and Indonesian non-Chinese still occurs, even though the integration is getting better. For this reason, researchers want to broaden the view of Chinese people's life from childhood, adolescence, and adulthood. In this study, the researchers used ethnographic methods to explore and telescope the story of growing up. According to James P. Spradley (2006: 5), ethnographic research aims to find the meanings of actions from events that happen to people we want to understand. A number of meanings are conveyed through language. This is a continuation of the previous study which have presented the results of interviews with three informants. This study will discuss the results of interviews with three other informants. Three informants were interviewed, namely three women named Mei (44 years old), Henny (43 years old) and Devi (22 years old) live in a fairly close location in the province of Banten. Mei and Devi, who are from the lower middle class, do not feel the difference between themselves and other children in Indonesia, even though they are both Indonesian-Chinese. Mei is more focused on issues of social and economic status that distinguish her from other children, while Devi is more focused on the departure of her father from the family. On the other hand, Henny as a child experienced restrictions on socializing from her parents with non-Chinese friends due to fears of being bullied. However, as she grew older, she became freer to choose her associates with non-Chinese friends, and she had quite a pleasant experience.